Mikroskładniki w leśnych glebach rdzawych Wału Zielonogórskiego = Microelements in forest rusty soils of the Zielona Góra Moraine Bar - Wawrzyniak-Gramacka, Edyta; Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents results of studies on content of Cu, Zn, Ni, Pb, Mn and Co in rusty soils. Soil samples were collected from the genetic levels of soils located within the Zielona Góra Moraine Bar. It has been concluded that the soils can be classified to ones of normal content of heavy metals with slightly enriched organic levels. The soil profiles from eastern part of Zielona Góra embankment are characterized by a considerably higher level of Mn, Pb and Co, comparing to its western part.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); mikroskładniki; gleby leśne; gleby rdzawe; Wał Zielonogórski; microelements; forest soils; rusty soils; Zielona Góra Moraine Bar, the